Onomastic Space of Animated Films about Russian Heroes by the Studio of Animation Cinema “Mill” - E. N. Ilyina; V. S. Tivo (Научный диалог)
The article is devoted to the study of the system of proper names in the texts of animated films with a folklore precedent basis. The relevance of the research is due to the need to study media texts that translate folklore imagery in linguocognitive and linguostylistic aspects. The material for the research is character and voice-over texts of animated films about Russian heroes: “Alyosha Popovich i Tugarin Zmey” (2004), “Dobrynya Nikitich i The Zmey Gorynych” (2006), “Ilya Muromets I Solovey Razboynik” (2007). The complex of names of geographical objects, the naming system of anthropo- and zoomorphic characters is considered, the precedent base for the formation of the onomastic space of animated films is determined, and the ways of introducing new components to the proper names system of this content are characterized. Special attention is paid to the description of intertextual links of the polycode content under study with works of epic genres of Russian folklore and with other sources. The scientific novelty of the work is seen in the fact that the verbal component of the studied animated films is currently insufficiently studied, and their proper names system becomes the subject of linguistic analysis for the first time.